Investigation of indoor thermal comfort of heritage buildings in hot summer and cold winter zone of China: A case study - Danqiu He; Mohd Hafizal Mohd Isa (Case Studies in Thermal Engineering, 2024)
The heritage buildings of a country or region are frequently considered to be of value and significance to the current generation. This study investigates the winter indoor thermal comfort of heritage buildings in hot summer and cold winter zone of China. Field measurements and questionnaire surveys were used to conduct specific studies on the winter indoor thermal comfort of two typical traditional residential buildings (“Yinziwu” and “Diaojiaolou”) in the Yuan River basin heritage building area. The aim is to investigate the current status of building thermal comfort and provide a theoretical basis for promoting their sustainable development. The results show that 1) Indoor air temperatures in both types of buildings are significantly and positively correlated in winter, but both are below the human thermal comfort range. 2) Mean air temperatures measured in ''Yinziwu'' and ''Diaojiaolou'' are 8.8 °C and 9.4 °C, respectively, with neutral air temperatures of 11.1 °C and 13.8 °C. 3) Thermal sensation, thermal preference, and thermal comfort were significantly correlated in the two buildings, with ooccupants experiencing the coldest phase from 7:00–11:00 and the warmest phase from 15:00–19:00 daily. 4) ''Yinziwu'' occupants are more tolerant of the cold climate.